Reducing depression during the menopausal transition with health coaching: Results from the healthy menopausal transition randomised controlled trial. (October 2016) - Almeida, Osvaldo P.; Marsh, Kylie; Murray, Karen; Hickey, Martha; Sim, Moira; Ford, Andrew; Flicker, Leon
Highlights: The menopausal transition is considered a time of increased vulnerability to depression. We used health coaching to address risk factors associated with depression during the menopausal transition. Compared with usual care, health coaching led to a greater decline in the severity of depressive symptoms over 12 months. Women with sub-threshold symptoms of depression at baseline benefited most from the intervention. Health coaching could play a useful role in decreasing mental health disturbances associated with the menopausal transition. Abstract: Objective: To determine if health coaching (HC) decreases the incidence of depression, reduces the severity of symptoms, and increases quality of life during the menopausal transition (MT). Research design and methods: Parallel, single-blinded, randomised controlled trial of 6 sessions of phone-delivered HC compared with usual care. Participants were 351 community-dwelling women free of major depression going through the MT, of whom 180 were assigned the intervention and 171 usual care. The primary outcome of interest was the incidence of clinically significant depressive symptoms over 52 weeks. Other study measures included the Hospital Anxiety and Depression Scale, quality of life (SF-12), the Menopause Rating Scale (MRS), diet, body mass index, alcohol use, smoking and physical activity. We considered that women with Patient Health Questionnaire (PHQ-9) scores between 5 and 14 (inclusive) had sub-threshold depressive symptoms. Results: Nine women developed clinically significant symptoms of depression during the study—2 had been assigned HC (odds ratio, OR = 0.26, 95%CI = 0.05, 1.29; p = 0.099). Intention-to-treat showed that, compared with usual care, the intervention led to a greater decline in depressive scores, most markedly for participants with sub-threshold depressive symptoms. Similar, but less pronounced, benefits were noticed for anxiety scores and the mental component summary of the SF-12. The intervention led to a decline in MRS scores by week 26 and subtle improvements in body mass, consumption of vegetables and smoking. Conclusions: HC addressing relevant risk factors for depression during the MT improves mental health measures. Our findings indicate that women with sub-threshold depressive symptoms may benefit the most from such interventions, and suggest that HC could play a useful role in minimizing mental health disturbance for women going through the MT.